Safety management of cranes on construction sites in Portugal: Critical factors of safety - Sousa, Flávia da Rocha (2015)
The evolution of the construction caused a need to use more effective equipments, capable of meeting the increasingly demanding deadlines for the completion of works. In this context, the safety and efficiency of equipment have become key aspects in order to optimize the execution time of the works, as well as reducing labor costs and loss of materials. With the evolution of construction and construction processes, cranes have come to represent a signal of the construction of buildings, revealing to be, in most of the cases, the main equipment of construction sites. Currently, some engineers revels some apprehension regarding the use and handling of cranes which is natural and acceptable, since an equipment failure can lead to serious or fatal accidents. The factors affecting safety management of the cranes in construction sites were investigated, identified, classified and evaluated according to their degree of importance, through interviews with representatives of the general contractors of a set of selected construction sites.